Implications of the Constitutional Court Decision number 83/PUU-XXII/2024 on the Procedure and Proof of Policy Claims in Life Insurance Disputes - Reza Yuda; Kamal Ubaidillah (Universitas Negeri Semarang, 2026)
Life insurance disputes in Indonesia often reveal a significant power imbalance between policyholders and insurance companies, which is traditionally exacerbated by Article 251 of the Commercial Code (KUHDagang) which allows unilateral cancellation of policies by insurance companies. This study aims to comprehensively examine the implications of the Constitutional Court Decision No. 83/PUU-XXII/2024 regarding the procedures and requirements for proving policy claims in life insurance disputes. This research adopts a normative juridical approach, utilizing qualitative descriptive-analytical methods to evaluate legal documents, norms, and principles. These findings indicate a paradigm shift from an insurance company-centric process to a balanced common legal framework. The Constitutional Court's decision eliminated the right of insurers to unilaterally cancel policies based on misrepresentations, now mandating collective bargaining or binding court decisions. As a result, the burden of proof is rebalanced, forcing insurers to undertake strict pre-event underwriting and proving material misrepresentation during dispute resolution. In conclusion, the ruling fundamentally restored the constitutional rights and legal certainty of policyholders. However, to fully realize this fair procedural shift, regulatory bodies and industry must implement operational harmonization, including revising standard policy clauses, establishing clear material evidence guidelines, and strengthening non-litigation mediation mechanisms.